How well do European patients understand cancer-associated thrombosis? A patient survey. (2022) - Falanga, Anna; Girvalaki, Charis; Monreal, Manuel; Easaw, Jacob C; Young, Annie
Abstract: Ongoing concerns regarding the morbidity and mortality from cancer-associated thrombosis led the European Cancer Patient Coalition (ECPC), the voice of cancer patients across Europe, to create a pan-European cancer-associated awareness patient survey to assess cancer-associated thrombosis (CAT) knowledge among a large population of patients with cancer. The ECPC survey represents the largest of its kind among patients/caregivers with CAT. It identified significant gaps in patient awareness and knowledge of CAT as well as a need for educational CAT-related discussions and interventions between healthcare professionals and patients with cancer and their caregivers. The aim of this paper is to highlight these gaps and to provide awareness of what/when information should be shared with patients/caregivers. Notably, the importance of providing information on how to reduce their risk of CAT, the role of anticoagulant prophylaxis and treatment (short- and long-term) including possible side-effects, and finally how to identify CAT symptoms early. Here we outline what type of information should be provided, as well as when and how to best discuss CAT with our oncology patients and their caregivers along the cancer care continuum, to reduce the risk of CAT and associated complications with a goal of improving patient outcomes. Graphical abstract: Image, graphical abstract .